2015
DOI: 10.14814/phy2.12547
|View full text |Cite
|
Sign up to set email alerts
|

The effects of buthionine sulfoximine treatment on diaphragm contractility and SERCA pump function in adult and middle aged rats

Abstract: This study examined the effects of 10 days of buthionine sulfoximine (BSO) treatment on in vitro contractility and sarcoplasmic reticulum calcium pump (SERCA) expression and function in adult (AD; 6–8 months old) and middle aged (MA; 14–17 months old) rat diaphragm in both the basal state and following fatiguing stimulation. BSO treatment reduced the cellular concentrations of free glutathione (GSH) by >95% and oxidized glutathione (GSSG) by >80% in both age cohorts. GSH content in AD Control diaphragm was 32%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…Recent studies demonstrated that inflammatory lesions also played an important role in myocardial ischemia-reperfusion injury (25,26). IL-6 is a cytokine that is mainly secreted from monocytes, macrophages and T/B lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that inflammatory lesions also played an important role in myocardial ischemia-reperfusion injury (25,26). IL-6 is a cytokine that is mainly secreted from monocytes, macrophages and T/B lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…GSH exists as the biologically active reduced-thiol form, and its oxidation to GSSG is associated with oxidative stress (OS). The GSH/GSSG ratio is around 100/1; when GSSG increases, this ratio decreases causing an oxidative shift in the cellular redox state[ 31 ]. Intestinal GSH redox homeostasis is maintained by de novo synthesis[ 32 ], regeneration from GSSG[ 33 ] and GSH uptake that derives from the dietary intake and mainly from the biliary output because the bile is enriched in GSH (1-2 mmol/L)[ 34 , 35 ].…”
Section: Gsh Synthesis and Its Physiological Role In The Intestinementioning
confidence: 99%
“…The mice lacking Sod1 show increased oxidative damage to DNA, proteins and lipids in skeletal muscle, and other tissues that is associated with muscle atrophy and functional decline. More specifically, these muscles show increased 3‐nitrotyrosine content, which is known to disturb SR protein function and the muscle contractile force …”
Section: Introductionmentioning
confidence: 99%